Dynamic Impacts of Lockdown on Domestic Violence: Evidence from Multiple Policy Shifts in Chile - Bhalotra, Sonia; Brito, Emilia; Clarke, Damian; Larroulet, Pilar; Pino, Francisco (The Review of Economics and Statistics, 2026)
Abstract We identify dynamic impacts on domestic violence (DV) of the staggered imposition and lifting of lockdown across Chile’s 346 municipalities. Lockdown increases DV helpline calls and shelter occupancy without increasing DV police reports. These results are consistent with lockdown raising incidence and creating barriers to reporting. Once lockdown is lifted, shelter occupancy falls and police reports surge, but helpline calls remain elevated in line with state dependence in DV. We identify male job loss as a mechanism driving DV. Our findings accentuate controversy around welfare impacts of lockdown mandates. Adverse impacts of lockdown on DV are mitigated by cash transfers.